Productivity of Different Local Sheep Breeds Fed by Water Spinach Straw - Hamdani Maulana; Endang Baliarti; Astrid Listia Astrini (Faculty of Animal Science, Universitas Gadjah Mada, 2021)
The decline in forage production during the dry season has an impact on the growth performance of livestock at the level of smallholder. The development of agricultural system by utilizing dried agricultural by-product is an alternative solution to the problem of limited feed during the dry season. Production of water spinach reaches 12,697 tons of dry matter/year and has potential to be used as a fiber sources for livestock. Studies on the use of water spinach straw (WSS) as feed for local sheep have not been widely carried out. This study was aimed to determine the productivity of Garut sheep (GS) and thin tailed sheep (TTS) fed water spinach straw. The results of this study were expected to provide information on the use of dry WSS as a substitute for forage for local sheep for fattening purposes. GS (n = 26) and TTS (n = 27) with an age of 8-12 months and body weight ranging from 10-20 kg were feedlots for 42 days. Sheep are kept intensively in colony pens (4-5 head/pen) with an approaching of body size and body weight. Feeding is done every morning and evening. Drinking water is always available. WSS is given ad libitum and the concentrate is given increasing periodically according to the treatment phase, Starter (1-14 days), Grower (15-28 days), and Finisher (29-42 days). Data were analyzed using One way ANOVA, operated by SPSS 20.0 program. The results showed that GS and TTS had no significant differences in productivity (gain, average daily gain, feed conversion ratio, feed cost, and feed cost per gain) (P>0.05). GS and TTS had the highest gain in the starter phase (2.04±1.08kg and 1.99±1.02kg, respectively) then decreased in the grower phase (1.46±0.83 kg and 1, respectively. 55±0.77 kg) and the finisher (1.61±0.77 kg and 1.59±0.74 kg, respectively). Based on the results obtained, it can be concluded that the GS and TTS had good productivity when fed by WSS as basal feed.